Statin utilisation patterns in older Australians living in residential care: 1‐year prevalence study. Issue 1 (January 2015) - Gnjidic, D.; Wilson, N.; March, L.; Cumming, R. G.; Cameron, I. D.; Hilmer, S. N.
Abstract Despite controversy over the risks and benefits of statin therapy, statins continue to be commonly used medicines by older people. In a cohort study of participants aged ≥70 years (n = 540) living in residential care, Sydney, we found that the proportion of statin users decreased gradually from the baseline of 33.1% to 31.3% at 6 months (P = 0.13) and to 28.7% over 1 year (P = 0.002). Prevalence of statin use decreased with increasing age, with individuals aged ≥90 years being more likely to discontinue or deprescribe statins. The patterns of statin use did not change according to increasing baseline dose or baseline indication.